Effect of support from lecturers and host country nationals on cross-cultural adjustment among international students: Evidence from a Malaysian University - Hak Liong Chan; Abdul Rahman Yaakob; Saizal Pinjaman (UPM Press, 2021)
Pursuing higher education abroad is a golden opportunity for any student’s personal development; however, international students’ cross-cultural adjustment (CCA) can be onerous in a foreign country. The purpose of this study is to empirically examine the roles of perceived lecturer support and host country national (HCN) support in international students’ CCA in three dimensions, i.e. general, academic, and interaction. Adopting the purposive sampling technique, survey data was collected from a sample of 124 first-year international students in a Malaysian university. The results of the partial least squares structural equation modelling analysis showed that both perceived lecturer support and HCN support are influential in international students’ general, academic, and interaction adjustment. These findings suggest that higher education institutions should amplify the role of lecturers and HCNs to help international students adjust to the various cultural aspects in Malaysia. This study contributes to the literature by applying the anxiety and uncertainty management theory to validate the influence of support on CCA in the international student context.